2015
DOI: 10.1016/j.jcrs.2015.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Near and intermediate reading performance of a diffractive trifocal intraocular lens using a reading desk

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
3
20
1
3
Order By: Relevance
“…When analyzing the reading performance, it is also important to make sure the reading acuity was measured with a reading speed of at least 80 wpm, because this threshold demonstrates that the print size was read easily without effort. 8 In the current study, all reading acuity values were measured with a reading speed of at least 80 wpm (range: 81 to 424 wpm), suggesting the patients' ability to perform daily tasks at intermediate and near distances comfortably.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…When analyzing the reading performance, it is also important to make sure the reading acuity was measured with a reading speed of at least 80 wpm, because this threshold demonstrates that the print size was read easily without effort. 8 In the current study, all reading acuity values were measured with a reading speed of at least 80 wpm (range: 81 to 424 wpm), suggesting the patients' ability to perform daily tasks at intermediate and near distances comfortably.…”
Section: Discussionmentioning
confidence: 57%
“…Currently, only a limited number of studies have assessed the reading acuity after implantation of different multifocal IOLs using this device. [8][9][10]22,23 Attia et al 10 examined the reading ability after bilateral implantation of another EDOF lens, the Tecnis Symfony IOL, and found a distance-corrected intermediate reading acuity of 0.00 logMAR at a fixed distance of 80.1 cm and 0.08 logMAR at a subjectively preferred distance of 65.0 cm (15 patients, 2 to 6 months postoperatively). For near, the distance-corrected near reading acuity was 0.29 logMAR at a fixed distance of 40.6 cm and 0.16 logMAR at a subjectively preferred distance of 41.7 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, contrast sensitivity has also been found to be stable between 1 and 12 months postoperatively [9]. As regards the distances at which intermediate and near visual acuity were evaluated, studies performed with a reading desk have reported that the preferred intermediate distance ranges between 61.50 cm and 64.20 cm [14, 16]; 60 cm was chosen because it is very similar to this preferred range and has been already used in other publications [4, 5, 15], facilitating comparison with studies performed with other IOLs. Similarly, the mean reported preferred near distance ranges between 34.6 cm and 38.70 cm [14, 16] and 33 cm was chosen as the distance to evaluate near vision as used in one other study which compared two trifocal IOLs [15].…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы на рынке стали доступны новые модели панфокальных (panfocal) ИОЛ, обеспечивающие пациенту больший комфорт при чтении на среднем расстоянии, чем более ранние бифокальные ИОЛ. Первые результаты имплантации таких ИОЛ, как FineVision® (Physiol, Бельгия) и AT LISA tri839MP® (CarlZeiss Meditec, Германия), являются весьма обнадеживающими [17][18][19][20][21][22][23][24][25][26][27]. С целью улучшения передачи света и его распределения между тремя фокусными точками была разработана новая мультифокальная ИОЛ -AcrySof PanOptix® trifocal (Alcon, США) [28].…”
Section: Ophthalmology In Russia 2019;16(1):19-25 введениеunclassified